Brief Periods of Sunshine: A History of the Canadian Government’s Attempt to Build a Solar Heating Industry, 1974-1983 - Trim, Henry (Scientia Canadensis, 2011)
In the 1970s a worldwide energy crisis wracked Canada. Searching for ways to provide energy for Canada’s future, the Canadian government encouraged the development of a new technology: solar heating. The political and economic needs of the Trudeau government and Department of Energy, Mines, and Resources dominated the Canadian solar heating industry from its inception in 1978 until its demise in 1983. Partisan politics, however, were not the only important influence on solar energy in Canada. Technologies of simulation and prediction, as well as the Canadian government’s adherence to the ideology of objectivity, also shaped the history of solar heating in Canada. By analyzing the role of simulation, “objectivity,” and political power in the rise and fall of the solar industry, this essay hopes to illuminate the importance of government in the Canadian history of technology and begin to provide a history of Canadian solar technology and industry.